1997
DOI: 10.1002/(sici)1097-0134(199702)27:2<165::aid-prot2>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Stability of secondary structural elements in a solvent-free environment: the α helix

Abstract: The stability of the alpha helix as an element of secondary structure is examined in the absence of solvation, in the gas phase. Mass-analyzed ion kinetic energy (MIKE) spectrometry was applied to measure intercharge repulsion and intercharge distance in multiply protonated melittin, a polypeptide known to possess a stable helical structure in a number of different environments. The experimental results, interpreted in combination with molecular mechanics calculations, suggest that triply charged melittin reta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 36 publications
3
61
0
Order By: Relevance
“…Other than the "end effects", the correlations between the stability maps in the condensed phases and gas phase for 3ϩ and 4ϩ melittin ions indicate that gaseous melittin ions up to four charges have a similar secondary structure as melittin in the condensed phases. This conclusion is consistent with the previous result that triply charged melittin retains its condensed phase secondary structure in the gas phase, as studied by intercharge repulsion measurement and molecular mechanics calculation [51]. For the 5ϩ melittin ion, as seen in Figure 3, a major conformational change occurs as indicated by the flexible Nterminal and C-terminal regions.…”
Section: Gas-phase Conformation Of Melittinsupporting
confidence: 92%
See 1 more Smart Citation
“…Other than the "end effects", the correlations between the stability maps in the condensed phases and gas phase for 3ϩ and 4ϩ melittin ions indicate that gaseous melittin ions up to four charges have a similar secondary structure as melittin in the condensed phases. This conclusion is consistent with the previous result that triply charged melittin retains its condensed phase secondary structure in the gas phase, as studied by intercharge repulsion measurement and molecular mechanics calculation [51]. For the 5ϩ melittin ion, as seen in Figure 3, a major conformational change occurs as indicated by the flexible Nterminal and C-terminal regions.…”
Section: Gas-phase Conformation Of Melittinsupporting
confidence: 92%
“…In the absence of solvent, intramolecular hydrogen bonds are much stronger because of the lack of competition from polar solvent molecules. In that respect, vacuum can be viewed as an ultimate nonpolar environment [51].…”
Section: Vacuum As a Nonpolar Environmentmentioning
confidence: 99%
“…In organic solvents, melittin exists in an ␣-helical form with two ␣-helices, one at each end, connected by a nonhelical hinge around Pro14 [40]. In their mass-analyzed ion kinetic energy (MIKE) spectrometry studies, Kaltashov and Fenselau have shown that triply charged melittin ion probably retains this helical structure in the gas-phase [41]. The conclusion was drawn based on a single parameter of intercharge distance between Lys7 and Arg22/24, the proposed charged sites, as determined by kinetic energy release accompanying fragmentation.…”
Section: Correlation Of Fragment Ion Survival Ratios With Gas Phase Cmentioning
confidence: 99%
“…In order for the internal exchange to occur, the two exchanging sites must come into direct contact with one another (akin to a bimolecular H/D exchange reaction in the gas phase). Lack of such flexibility due to either (partial) retention of the solution structure in the gas phase (121) or the "cementing" role of metal cations (122) would limit the extent of scrambling. These simple considerations suggest that the best chance of avoiding hydrogen scrambling in the gas phase would result from employing fast (high-energy) ion fragmentation methods and using solution conditions that allow proteins to remain (partially) structured.…”
Section: "Top-down" Approaches To Probing the Local Structure Of Intementioning
confidence: 99%